2016
DOI: 10.17140/hartoj-3-119
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS and Contraceptive Method Choice: Demographic and Socio-Economic Correlates of Contraceptive Method Choice among HIV-Positive Women Practising Family Planning In Kenya

Abstract: CitationAs the generalized HIV epidemic in specific settings of sub-Saharan Africa continues to evolve, there is need for evidence-based response to address emerging challenges, which include enabling the large number of women living with HIV make informed choices to achieve their reproductive goals. Objectives: This paper seeks to (i) examine the effect of HIV/AIDS on contraceptive method choice among women using contraceptives in Kenya; and (ii) identify correlates of contraceptive method choice among HIV-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Besides, it has been observed that even where no evidence of a significant relationship between HIV status and unintended fertility is apparent, HIV-positive women are likely to make greater efforts than HIV-negative women to prevent unintended fertility, but with less success (Bankole et al 2014). HIV-positive women may be predisposed to a higher risk of unintended fertility due to disproportionate reliance on less effective contraceptive methods such as condoms or periodic abstinence (Wall, et al, 2013;Schaan et al, 2014;Magadi, 2016), with low practice of dual protection (Berer 2006).…”
Section: The Link Between Hiv/aids and Fertility Intentionsmentioning
confidence: 99%
“…Besides, it has been observed that even where no evidence of a significant relationship between HIV status and unintended fertility is apparent, HIV-positive women are likely to make greater efforts than HIV-negative women to prevent unintended fertility, but with less success (Bankole et al 2014). HIV-positive women may be predisposed to a higher risk of unintended fertility due to disproportionate reliance on less effective contraceptive methods such as condoms or periodic abstinence (Wall, et al, 2013;Schaan et al, 2014;Magadi, 2016), with low practice of dual protection (Berer 2006).…”
Section: The Link Between Hiv/aids and Fertility Intentionsmentioning
confidence: 99%